Impact of Knowledge and Attitude Over Practices and Reporting of Needle Stick Injuries among Dental Healthcare Providers - BANA, Kiran Fatima Mehboob Ali (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To assess unreported cases of needle stick injuries (NSIs) and to find association between awareness, attitude, practices with unreported odds of NSIs. It was hypothesized that more than 50% NSIs are unreported. METHODOLOGY: It was cross sectional study design executed in Karachi among the dental care providers from July - September 2018. The calculated sample size was 281 which was augmented as 396. Total 312 questionnaires were completely filled. The data was analyzed on SPSS version 23. Association between categorical variable were assessed by Chi square/ Fischer exact test. RESULTS: Total n=195(62.5%) subjects experienced NSIs during clinical practice; from which n=110(56.4%) were unreported and n=85(43.5%) were reported cases in individual’s working setup. Majority of the subjects were aware of the harms of NSIs but not reporting the cases in clinical settings. From the to tal sample (n=231-74%) were aware of the needle safety device but (n=139-60%) were not reporting the incidence at p-value of 0.043-graph-1. Total (n=294-92%) participants were in favor of the need of strong reporting system of NSIs. On the other hand; majority of the study participants were practicing the preventive measures against NSIs but more than 50% were not reporting the NSIs; there was significant difference found for wearing gloves for disposing contamination and bent needle before dispose but not reporting the NSIs at p-value of 0.012 and 0.003 respectively CONCLUSION: It was inferred that more than 50% needle stick injury cases were unreported among dental personnel despite of having sufficient awareness, attitude and practices towards safe clinical practice. Keywords: Cross Infection Control, Dental Work Force, Needle Stick Injury, Unreported.